2020
DOI: 10.1155/2020/5072989
|View full text |Cite
|
Sign up to set email alerts
|

An Analytical Procedure to Predict Transverse Vibration Response of Jack-Up Riser under the Random Wave Load

Abstract: Marine riser is a key equipment in offshore drilling operation, and failure of the riser can lead to drilling moratorium; in severe cases, it may cause oil and gas leaks. In this paper, the time-dependent boundary conditions of the riser and the randomness of wave load are considered to improve the calculation efficiency and accuracy of the dynamic response of the jack-up riser. Based on the Euler–Bernoulli beam theory, an analytical method to determine the response of the jack-up riser subjected to the random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The dispersed energy spectrums appear in the vibration study of marine risers with time-varying boundary conditions and wave loads. 29 This phenomenon of energy transfer has been detected in the study of an axially accelerating viscoelastic beam. 30 The modal interactions from internal resonance cause significant variation of the steady-state responses.…”
Section: Introductionmentioning
confidence: 87%
“…The dispersed energy spectrums appear in the vibration study of marine risers with time-varying boundary conditions and wave loads. 29 This phenomenon of energy transfer has been detected in the study of an axially accelerating viscoelastic beam. 30 The modal interactions from internal resonance cause significant variation of the steady-state responses.…”
Section: Introductionmentioning
confidence: 87%
“…Wang et al proposed an analytical method to predict the transverse vibration response of a jack-up riser under random wave load, which is based on Euler-Bernoulli beam theory and Mindlin-Goodman method in the frequency domain. Experimental verification was conducted to validate the accuracy of the proposed method [10]. Several studies have demonstrated that both the top tension and internal fluid play crucial roles in influencing the dynamic response of the riser [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…e SCR is a typical high flexible structure with a long span and low damping, making it susceptible to oscillations induced by a variety of internal and external sources [4]. During the past decades, extensive studies have been carried out to investigate the behavior of an SCR under vortexinduced vibration [5], internal slug flow-induced vibration [6], external flow-induced vibration [7], and vibration caused by the motion of the floating platform or other types of oil vessel [8,9], among others.…”
Section: Introductionmentioning
confidence: 99%